Dictionary of Cape Breton English - Davey, William J., 1944-; Davey, William J., 1944-; MacKinnon, Richard Paul, 1957-; MacKinnon, Richard Paul, 1957- (Book collections on Project MUSE., 2016)
"Biff and whiff, baker's fog and lu'sknikn, pie social and milling frolic--these are just a few examples of the distinctive language of Cape Breton Island, where a puck is a forceful blow and a Cape Breton pork pie is filled with dates, not pork. The first regional dictionary devoted to the island's linguistic and cultural history, the Dictionary of Cape Breton English is a fascinating record of the island's rich vocabulary. Dictionary entries include supporting quotations culled from the editors' extensive interviews with Cape Bretoners and considerable study of regional variation, as well as definitions, selected pronunciations, parts of speech, variant forms, related words, sources, and notes, giving the reader in-depth information on every aspect of Cape Breton culture."--